Comparison of uroflow parameters in children with pure constipation versus constipation plus lower urinary tract symptoms - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2015)
Objective: The aim of this study was to compare uroflow parameters of patients with pure constipation against those with constipation plus lower urinary tract symptoms (LUTS) and a control group (no constipation). Materials and methods: During August 2012 to March 2014 three groups of patients were enrolled into the study: group C (constipation only), group CL (LUTS plus constipation) and group N (control: no constipation or LUTS). Dysfunctional elimination syndrome (DES) scores, uroflowmetry/electromyography (uroflow-EMG) findings, postvoiding residual urine (PVR) and rectal diameter were measured and compared between groups. Results: Groups C, CL and N comprised 80, 100 and 30 patients, respectively. Average DES scores were 12.6, 18.7 and 4.9, respectively. Voided volume (as a percentage of expected bladder capacity) was 104%, 89% and 101%; and average maximum flow rate was 21.1 ml/s, 36.4 ml/s and 28.1 ml/s, respectively. Pelvic floor muscle activity during voiding was seen in 40.0%, 42.0% and 6.7% of patients in groups C, CL and N, respectively; and pathological PVR was seen in 26.3%, 55.0% and 3.3% of patients in the respective groups. Average rectal diameter was measured as 38.6 mm, 36.4 mm and 28.1 mm in groups C, CL and N, respectively. Conclusion
Keywords: Constipation; lower urinary tract symptoms; uroflow; DYSFUNCTIONAL ELIMINATION SYNDROMES; OVERACTIVE BLADDER; DIAGNOSTIC-TOOL; INCONTINENCE; PREVALENCE; CHILDHOOD; ENURESIS; RECTUM